#### Answer

1. The function rule for this sequence would be
A(n)=5+4(n-1).
2. The first six terms would be 5, 9, 13, 17, 21, 25

#### Work Step by Step

The function was created using the explicit formulas I devised the values were increasing by 4 and that the sixth term was 25. Thus, I found the A(1) value using these two values.
A(6)=A(1)+4(6-1)
25 = A(1)+4(5)
25= A(1) +20
A(1) =5
2.
First term --> A(1)= 5+4(1-1). = 5+4(0) = 5
Second term --> A(2)= 5+4(2-1) = 5+4(1) = 5+4 = 9
Third term --> A(3)= 5+4(3-1) = 5+4(2) = 5+8 =13
Fourth term --> A(4)=5+4(4-1) = 5+4(3) = 5 + 12 = 17
Fifth term --> A(5)= 5+4(5-1) = 5+4(4) = 5+16 = 21
Sixth term --> A(6)= 5+4(6-1) = 5+4(5) = 5 +20 = 25